High School Athletes With ADHD and Learning Difficulties Have a Greater Lifetime Concussion History. Issue 8 (June 2020) - Iverson, Grant L.; Wojtowicz, Magdalena; Brooks, Brian L.; Maxwell, Bruce A.; Atkins, Joseph E.; Zafonte, Ross; Berkner, Paul D.
Objective: Examine lifetime history of concussions in adolescents who have developmental problems in comparison with those with no developmental problems.Method: Thirty-two thousand four hundred eighty-seven adolescent athletes completed baseline/pre-season evaluations. Based on self-reported histories, athletes were divided into four groups: ADHD only, ADHD and learning difficulties (LD), LD only, and controls.Results: Athletes with ADHD, LD, or ADHD plus LD reported a greater prevalence of prior concussions than athletes without these developmental conditions ( p s < .05). When adjusting for sex differences in concussion prevalence rates (boys are greater than girls), there was an increase in prevalence of prior injuries in those with ADHD, and ADHD plus learning difficulties compared with those with LD only. This pattern was found for both girls and boys. There was no additive effect of having both conditions.Conclusion: Developmental conditions in adolescent athletes, such as ADHD and learning difficulties, are associated with a greater prevalence rate of prior concussion.